The Oncometopia orbona species group (Hemiptera, Cicadellidae, Proconiini) - Rakitov, Roman (Zootaxa, 2016)
The Oncometopia orbona group of species is defined based on the characteristic structure of the male aedeagus. A key to males and females of 9 species is included, among which 5 are newly described from the U.S.A., Mexico, and Central America: O. orbona (F.), O. nigricans (Walker), O. obtusa (F.), O. clarior (Walker) (= Proconia badia Walker syn. n., Proconia scutellata Walker synonymy reinstated), O. hamiltoni sp. n., O. acicularis sp. n., O. lepida sp. n., O. pelvica sp. n., and O. unispina sp. n. The systematics of the group presents some unusual cases. In particular, O. lepida sp. n. and O. pelvica sp. n. differ from one another in the shape of the female genital chamber sclerites, but not in the male genitalia. Oncometopia nigricans is almost identical in the genitalic characters of both sexes to O. hamiltoni sp. n., from which it is dissimilar externally, as confirmed by morphometric analysis, but is externally similar to O. orbona, from which it strongly differs in both the male and female genitalia. The rare intermediate forms from northern Florida and southern Georgia are interpreted as orbona x nigricans hybrids. Oncometopia clarior is treated as a complex of species which at present cannot be separated.